Meningkatkan Motivasi dan Hasil Belajar PPKn Siswa Melalui Penerapan Pendekatan Cooperative Learning Tipe STAD di Kelas VII-E SMP Negeri 5 Mataram - Johariah, Baiq (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
This study aims to find the effectiveness of STAD type cooperative learning (CL) approach in an effort to improve students' learning motivation in grade VII-E SMP Negeri 5 Mataram. The benefit of this research is as references in the implementation of the learning process in the real class. For teachers,it is to improve competence in the teaching process and for students to improve learning motivation that impacts on students’ learning outcomes. This research was conducted two cycles and the activity for each cycle is; planning, action, observation and reflection. The final result of action in cycle II showed that the teacher observation result got average score (4,21) and the student observation reached average score (4,09). The impact of the increase in the students’ learning motivation reached the average value (87.94), meaning that indicator of the success (> 4.0) had been exceeded. Because the success indicator has been proven that the research is claimed successful and stopped in cycle II.